Bridging Cognitive and Social-Emotional Development Frameworks: Toward Responsive Learning Design in Indonesian Primary Schools - Muhammad Fadhil; Muh. Asharif Suleman; Chairul Bariyah; Chairan Zibar L. Parisu Parisu; Nourma Yulita (Journal of Contemporary Gender and Child Studies, 2025)
Diverse prior research reveals gaps in integrating cognitive and social-emotional development theories into primary school learning design, particularly within Indonesia's digital-era context. This study aims to develop a conceptual framework bridging both developmental aspects to design responsive learning in Indonesian primary schools. Employing an Integrative Literature Review, this study examined 65 national and international journal articles, academic books, and research reports published 2015-2025 through systematic search strategies, defined inclusion-exclusion criteria, and thematic analysis. Findings identify that child aged 7-11 years in the concrete operational stage require learning emphasizing hands-on experiences, concrete representations, and contextual activities. Integration of social-emotional aspects, self-awareness, emotion management, social relationships, and empathy, demonstrates significant correlation with learning motivation, classroom participation, and academic achievement. This study offers a comprehensive framework integrating Piaget's cognitive development theory with Social and Emotional Learning (SEL), generating five implementable strategies: differentiated instruction, experiential learning, systematic SEL integration, balanced technology utilization, and teachers' role as holistic facilitators. The conceptual contribution provides theoretical-practical foundations for developing responsive learning designs that comprehensively accommodate children's developmental needs in Indonesian primary schools.